Role of the teacher in Activating, Through Classroom Environment and Utilization of media learning Resources, the Teaching of the Geography course to third Grade (Year) Female students at the Girl School in the Holy City of Makkah - Maghrapi, Aliaa Hameid; Banjar, Fawzi Saleh (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed to highlight the role of the geography Female teacher in activating this subject when taught to third grade intermediate school female students studying at girls school in the Holy City of Makkah, through utilizing the local settings and the multiple learning Resources, and also disclosing landraces impeding the process of teaching. The researcher followed the descriptive methodology and designed a questionnaire that was administered to a sample of (72) geography Female teachers at the intermediate stage in the Holy City of Makkah. The study concluded with important results such as: the geography teacher plays a significant role in activating the teaching of geography achieving an arithmetic mean of (3.73) to (4.51) and most prominent hindrances laundering the use of learning resources in teaching geography were overcrowded classrooms and excessively large numbers of students in classrooms causing arithmetic mean of (3.94) and a role at a medium level. The number of geography teaching periods in the teacher's schedule was very low as a teaching load with arithmetic mean of (2.79). The study also found no statistically significant difference between the responses of the geography teachers that could be attributed to the "age" and of number of years of experience variables. The study concluded with same recommendation of which were: Augmenting the number of teaching period in the academic weakly schedule of teachers at the intermediate school and the need for the geography teachers to rely an effective teaching media that aid the teaching learning process as well as modern projection apparatuses. The study proposed the conduction of research surveys and quasi-exponential studies in the employment of learning resources in teaching geography at the intermediate and secondary school cycles.
Keywords: Geography curriculum; third intermediate grade; Saudi Arabia; classroom environment; learning resources; learning obstacles; teacher's role